CYCLICAL DYNAMICS OF THE «EXTERNAL» AND «INTERNAL» ENVIRONMENTS OF BUSINESS-ORGANIZATIONS IN GR-MANAGEMENT - A. A. Degtyarev; М. D. Bondarev; A. S. Teteryuk (Vestnik MGIMO-Universiteta)
Within current conditions large business seeks to more actively influence processes of public state policy formulation and implementation connected with regulation of the economy and allocation of public resources. To ensure growing and systemic influence on the processes of government decision making, corporations promote economic interests by creating systems of controlled communications and relations with state bodies (SB). This field of professional activity identified as «GR» (Government Relations) is a specific type of management activity, specific cross-sectoral (cross-area) management of interactions between business companies (and other non-state actors) and the state authorities, located at the crossing of three basic sectors of governance (government, business and social (nonprofit) organizations). Professional functions on establishing and maintaining relations between business and government are conducted by GR-departments of large companies, specialized consulting firms and business associations. The complexity of those activities for business organizations proceeds from its specific location at the intersection of two environments (sectors): internal (in-house) and external (political and public) ones. This means that GR-specialist tries to consider the interests of these counterparties and identify points of intersection, where common interests can develop into business cooperation, and this may also contribute to the constructive involvement of business in shaping public policy. During such activities GR-specialist regularly faces the practical problems of frequent temporary error (“temporal asynchrony”) and low level of spatial contingency (“spatial incongruence”) between the “sectoral (environmental)” types of managerial dynamics and their autonomous rhythms and paces, special sectoral functioning and development strategies, deployed within each of these sectors (industry business strategy vs public policy area) and specific phases of the cycles of corporate and public governance, yet weakly interlinked. The authors stem from the common idea according to which a basic methodological prerequisite for the analysis, design and implementation of the effective and efficient GR-work is the development of a cycle model of the so-called “cross-sectoral” management, which would consider complex dynamics of the «internal» corporate processes as well as «external» public-management cycles.